2016
DOI: 10.1136/bmjopen-2015-009929
|View full text |Cite
|
Sign up to set email alerts
|

Disaster anxiety and self-assistance behaviours among persons with cervical cord injury in Japan: a qualitative study

Abstract: ObjectivesPersons with disabilities, especially those with a severe disability, have a vague anxiety about future disasters; however, the measures of self-assistance for disaster preparedness have not been standardised. The present study aimed to describe disaster-related anxiety and behaviours related to disaster preparedness among persons who have cervical cord injury in Japan.DesignQualitative study.SettingTokyo Metropolitan area, Japan.Participants16 persons with cervical cord injury participated. Inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…This research indicates that disaster preparedness is extremely important to maintain individual mental health and to meet the basic needs of life in the event that a government announces a sudden lockdown to minimize the spread of a virus. The protective role of disaster preparedness for mental health might be because it helps individuals obtain a feeling of being well prepared, improves their sense of security, and increases the use of positive coping [ 30 , 31 ]. Therefore, interventions to promote disaster preparedness for vulnerable populations, including foreign residents, are a promising solution for minimizing the psychological impact of an unpredictable health emergency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research indicates that disaster preparedness is extremely important to maintain individual mental health and to meet the basic needs of life in the event that a government announces a sudden lockdown to minimize the spread of a virus. The protective role of disaster preparedness for mental health might be because it helps individuals obtain a feeling of being well prepared, improves their sense of security, and increases the use of positive coping [ 30 , 31 ]. Therefore, interventions to promote disaster preparedness for vulnerable populations, including foreign residents, are a promising solution for minimizing the psychological impact of an unpredictable health emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of an uncertain future disaster imposes constant pressure and psychological distress, as it has in the case of COVID-19 [ 29 ]. Disaster preparedness helps people feel prepared, improves their sense of security, and allows them to identify their feelings and manage their emotional responses to better cope with difficulties, thus reducing anxiety and depression [ 30 , 31 ]. Therefore, when individuals prepare for material and psychological aspects, fewer psychological symptoms may occur [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, concerns about future disasters can be a significant source of ongoing distress for survivors of chronic disasters; feeling adequately prepared may increase efficacy and perceived safety, and so decrease feelings of anxiety and depression (e.g. Galappatti and Richardson, 2016; Takahashi and Kitamura, 2016). Although little research has directly investigated this link, it follows that mental health-focused interventions for disaster vulnerable populations may benefit from inclusion of disaster risk reduction content.…”
Section: Introductionmentioning
confidence: 99%
“…This is also supported by another research found that using a qualitative study of respondents in Japan who have an interest in disaster preparedness and have self-help groups to be able to manage anxiety when they are dealing with disasters. 7 There are three themes associated with perceived anxiety, which are storing needed items, staying in a safe place and friends who can be invited to share to avoid anxiety. This shows the need for the closest support groups that the local community has to exchange ideas, information, and experiences in preparing so that local residents can jointly prepare properly when their regions face flooding by forming discussion groups.…”
Section: Resultsmentioning
confidence: 99%